Methotrexate polyglutamates - Yang, Zhilin; Mo, Jiayi; Li, Wenshu; Zhao, Zhigang; Mei, Shenghui (Expert review of clinical pharmacology, 2024)
Methotrexate polyglutamates (MTXPGs) are intracellular metabolites of methotrexate (MTX) that play a critical role in the drug's activity, influencing both its efficacy and toxicity. As the exact implications of MTXPGs in these processes remain a subject of debate, a comprehensive review of MTXPGs could provide valuable insights for clinicians and pharmacists, potentially minimizing adverse reactions and enhancing therapeutic outcomes. A comprehensive search of relevant literature was conducted in PubMed and Web of Science databases, including studies from their inception to April 2024. Eligible studies included reviews, clinical trials, and real-world analyses. Additional manual searches and citation reviews were also performed. This review aims to explore MTXPGs with a primary focus on their pharmacokinetics, analytical methods, determinants of drug exposure, and their correlation with MTX efficacy and toxicity. MTXPGs have not yet garnered significant attention in clinical practice. However, multiple studies have demonstrated a relationship between MTXPGs and the efficacy and toxicity of MTX, suggesting a potential avenue for personalized treatment strategies. Future research should aim to further validate and refine this correlation. Additionally, attention should also be directed toward other metabolites of MTX, which may hold clinical significance.